Estudio de la vegetación bentónica del litoral granadino - Varo, Juan; Ramírez Uña, J.; Rentería, J. (Universidad de Málaga, Servicio de Publicaciones, 1979)
Como primera fase del estudio de la investigación bentónica del Litoral Granadino, se han recolectado y clasificado 111 especies de las que 61 pertenecen a la División Rho,dophyta, 25 a la División Chlorophyta, 19 a la División Phaeophyta y 6 a la División Cyanophyta.

At the begining of the project of study about benthonic seaweeds in the litoral ofGranada (South Spain), 111 species were collected and determinated, distributed as following: 61 of the división Rhodophyta, 25 of the Chlorophyta, 19 of the Phaeophyta and 6 of the Cyanophyta.